Raster image correlation spectroscopy as a novel tool to study interactions of macromolecules with nanofiber scaffolds - Norris, S C P; Humpolíčková, J; Amler, E; Huranová, M; Buzgo, M; Macháň, R; Lukáš, D; Hof, M (Acta biomaterialia, 2011)
Dynamic processes such as diffusion and binding/unbinding of macromolecules (e.g. growth factors or nutrients) are crucial parameters for the design and application of effective artificial tissue materials. Here, dynamics of selected macromolecules were studied in two different composite tissue engineering scaffolds containing an electrospun nanofiber mesh (polycaprolactone or hydrophobically plasma modified polyvinylalcohol-chitosan) encapsulated in agarose hydrogels by a conventional approach fluorescence recovery after photobleaching (FRAP) and a novel technique, raster image correlation spectroscopy (RICS). The two approaches are compared, and it is shown that FRAP is unable to determine processes occurring at low molecular concentrations, especially accurately separating binding/unbinding from diffusion, and its results depend on the concentration of the studied molecules. RICS measures processes of single molecules and, because of its multiple adjustable timescales, can distinguish whether diffusion or binding controls molecular movement and separates fast diffusion from slow transient binding. In addition, RICS provides a robust read-out parameter quantifying binding affinity. Finally, the combination of FRAP and RICS helps to characterize diffusion and binding of macromolecules in tested artificial tissues better, and therefore predicts the behavior of biologically active molecules in these materials for medical applications.
Keywords: Nanofibers; difuze; nanovlákna; Protein Binding; Diffusion; vazba proteinů